Investigating the association between opioid analgesics and the risk of bone fracture - Peach, Emily J. (2020)
Background Opioids have been increasingly prescribed to people with pain; despite limited evidence to support their effectiveness and safety in the long-term. Opioids may increase the risk of bone fracture due to effects on the central nervous system (CNS) and on bone mineral density (BMD). The aim of this research was to examine the utilisation of opioids in the UK and to explore the relationship between opioids and fractures.